Phytotoxic potential of cultivated and wild potato species (Solanum sp.): role of glycoalkaloids, phenolics and flavonoids in phytotoxicity against mustard (Sinapis alba L.) - Sołtys-Kalina, Dorota; Murawska, Zofia; Strzelczyk-Żyta, Danuta; Wasilewicz-Flis, Iwona; Marczewski, Waldemar (Acta physiologiae plantarum, 2019)
The phytotoxic abilities of potato ( Solanum tuberosum L.), in a population consisting of wild species, potato diploid hybrids and potato cultivars, against mustard ( Sinapis alba L.) were investigated. Measurements of total glycoalkaloid, phenolic and flavonoid concentrations in potato leaf extracts and their role in phytotoxicity were performed. Extracts prepared from wild potato species, particularly Solanum maglia and Solanum chacoense , had the strongest inhibitory effect on mustard growth. Most extracts significantly extended the germination time, as determined by Piepper’s index, but extracts prepared from potato cultivars did not affect seedling growth/development. However, only S. maglia and S. chacoense prolonged the time of germination, corresponding to inhibition of mustard growth. The Pearson’s correlation coefficient of concentrations of total glycoalkaloids, phenolics and flavonoids in potato leaf extracts and length of mustard seedlings showed a significant negative correlation for glycoalkaloids ( r = − 0.51), with the strongest effect for root length of potato wild species ( r = − 0.79) and potato diploid hybrids ( r = − 0.86). Our data indicated that glycoalkaloids are the major phytotoxic compounds responsible for potato phytotoxicity against mustard. However, we observed phenolics and flavonoids may influence the strength of the phytotoxic effects caused by glycoalkaloids.